PENGARUH EFEKTIVITAS IKLAN YOUTUBE TERHADAP BRAND IMAGE - Helena, Monique; Natalia, El Chris (Universitas Brawijaya, 2021)
ABSTRACTAdvertising is used by companies as a way to market products and services. YouTube is currently the most popular social media in Indonesia and has become a platform of marketing the company's products and services. Head & Shoulders, which is under the auspices of the Procter & Gamble company uses YouTube in marketing and promoting its products. This research focuses on Joe Taslim's “Head & Shoulders” Bloopers YouTube ad. This study aims to determine the influence of the effectiveness of Joe Taslim's